War for Talent in Human Resource Management: Organizational Strategies for Attracting and Retaining Top Talent - Roberthair Suripatty; Victor P. K. Lengkong; Rita N. Taroreh; Christoffel M. O. Mintardjo (PT. Anagata Sembagi Education, 2026)
The intensifying global competition for skilled human capital, widely termed the